The Influence of the Local Wisdom-Based Pancasila Student Profile (P5) Strengthening Project on Student Entrepreneurship Skills - Waty, Arlyana Marhaendra; Syarifuddin; Nurdin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to 1) examine the implementation of the Strengthening Pancasila Student Profile Project (P5) based on local wisdom for Grade IV students of UPT SPF SDN Mangkura IV, 2) assess entrepreneurial skills of Grade IV students, and 3) analyze the influence of P5 on entrepreneurial skills. Using a quantitative approach, the research involved 39 students selected through saturated sampling. Data collection methods included questionnaires, observation, and documentation, analyzed using t-tests. Results reveal the P5 implementation faces challenges in planning, coordination, and assessment. Despite these, students demonstrated excellent entrepreneurial skills. Statistical analysis confirmed a positive and significant effect of P5 on entrepreneurial skills, with a t-value of 5.680 (p < 0.05), suggesting its efficacy in enhancing entrepreneurship education.